(untitled) (Sciences & Technology. A, exactes sciences, 2001)
A new model, based on a surface saturation technique, is suggested to determine grain boundary diffusivity of impurities. The model is applied to the Ni-S system that is of great practical interest. The initial saturation of nickel grain boundaries with sulphur is obtained by annealing at a temperature which satisfies the thermodynamics criterion for surface saturation. In order to reduce the annealing time, dynamic (non-equilibrium) segregation is induced by carrying out the anneal on cold worked nickel (e = 0.2 true strain). Both the grain boundaries and the surface were saturated after only 24 hours of annealing at a temperature as low as 450°C. The heat treatment of the cold rolled material was carried out inside the vacuum chamber of an Auger Electron Spectrometer (AES). The diffusivity, as obtained from the slope of the linear parts of the kinetics curves recorded by the AES, is found to be given by the relationship D = 2.7×10-9exp(-58.700/RT) m2s-1 in the temperature range 450 to 700°C.